Effects of Sweet Bee Venom on the Central Nervous System in Rats -using the Functional Observational Battery- - Joong Chul An; Ki Rok Kwon (Korean Pharmacopuncture Institute, 2011)
Objectives: This study was performed to analyse the effects of Sweet Bee Venom(Sweet BV-pure melittin, the major component of honey bee venom) on the central nervous system in rats. Methods: All experiments were conducted at Biotoxtech Company, a non-clinical studies authorized institution, under the regulations of Good Laboratory Practice (GLP). Male rats of 5 weeks old were chosen for this study and after confirming condition of rats was stable, Sweet BV was administered in thigh muscle of rats. And checked the effects of Sweet BV on the central nervous system using the functional observational battery (FOB), which is a neuro-toxicity screening assay composed of 30 descriptive, scalar, binary, and continuous endpoints. And home cage observations, home cage removal and handling, open field activity, sensorimotor reflex test/physiological measurements were conducted. Results: 1. In the home cage observation, there was not observed any abnormal signs in rats. 2. In the observation of open field activity, the reduction of number of unit areas crossed and rearing count was observed caused by Sweet BV treatment. 3. In the observation of handling reactivity, there was not observed any abnormal signs in rats. 4. In the observation of sensorimotor reflex tests/physiological measurements, there was not observed any neurotoxic signs in rats. 5. In the measurement of rectal temperature, treatment of Sweet BV did not showed great influences in the body temperature of rats. Conclusions: Above findings suggest that Sweet BV is relatively safe treatment in the central nervous system. But in the using of over dose, Sweet BV may the cause of local pain and disturbance of movement. Further studies on the subject should be conducted to yield more concrete evidences.